(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
The improvement of the direct control of flux and torque (DTC) essentially consists of reducing the ripples encountered at the levels of the torque and the stator magnetic flux. This control technique is widely used in various applications that recently employ the permanent magnet synchronous motor (PMSM). The improvement techniques are grouped into two large families: those that use multilevel inverters and require an additional cost to the driven system, which is only encouraging if the application covers this cost, and those that offer selection tables. This last solution is advantageous because it does not need any added device. In this paper, we propose to combine the two solutions, using a reduced switching table (RST) compared to the conventional switching table (CST) and using a four-level multicellular inverter (4LMI). This solution brought very satisfactory results by significantly reducing the ripples.